Çevresel bir faktör olarak kültür kavramı ve çokuluslu işletmelerde kültür gruplarına göre karşılaştırmalı bir inceleme (Ericsson) - Laplanche, Ayşe (My University, 1999)
Çokuluslu İşletmelerde, çevresel bir faktör olarak işletmenin ömrünü ve gelişimini etkileyen güçler arasında ulusal çevre, yabancı çevre, uluslararası çevreyi sayabiliriz. Çokuluslu işletmelerin yapısı incelendiğinde, bunların bir ana ülke (merkez) etrafında toplanan ve zamanla bütün dünyaya yayılan işletmeler gurubu olduğunu görüyoruz. İşletmelerin çokuluslaşması ve bir ülkenin sınırları dışına taşırak yapısal değişikliğe uğramalarıyla birlikte dünya ticaretinin şekil değiştirmesi, son yılların en önemli tartışma konularından biri olmaktadır. Dünyanın ekonomik ve sosyal gelişiminde önemli bir rol oynayan çokuluslu işletmele, gelişmiş ve gelişmekte olan ülkeler açısından da büyük önem taşımaktadır. Bununla birlikte çokuluslu işletmeler, kültürel gelişim sürecinde de önemli bir yere sahiptirler. Çünkü bu işletmeler, gittikleri yerlere ana ülkelerinin kültürlerini bereberlerinde getirirler. Tabii ana ülke kültürüyle evsahibi ülkenin kültürü arasında büyük farklar olabilir. Bu tür farklılıklar da çokuluslu işletmeler için bazı çekici ve itici faktörler oluşturur. Başka bir deyişle, farklı ülkelerde faaliyette bulunmak, farklı dillerin, farklı dinlerin,alişkanlıkların, kısacası farklı değer ve inançların yanında çeşitli sorunları da beraberinde getirmektedir. Çokuluslu işletmelerin derinden etkilediği Amerika, avrupa, Japonya ve Asya iş kültürleri arasında göze çarpan farklılıklar bu yazıda ayrıntılarıyla tanımlanmaktadır. Bu tez yazımızda uygulama olarak Ericsson firmasının Türkiye, Asya ve Amerika'daki işletmelerinin kültürel farklılıkları araştırılmıştır. Sonuç olarak her işletmenin kendine özgü bir kurum bir kültürü oluşturduğu görülmüştür. Yabancı ülkelerdeki ericsson işletmeleri işte bu kurum kültürlerini geliştirerek üretim ve pazarlama alanlarında başarıya ulaşmışlardır. Yüz yirmi bir yıldır alanında lider olan Ericsson firmasının başarısıbütün dünyada paylaşılan ortak değerlerin ve farklılıkların bir sonucudur. The Concept of Culture as an Environmental Factor and a Comparative Study based on Cultural Groups in Multinational Corporations: Ericsson It is possible to cite the domestic environment, the foreign and the international environment among the forces assumed to play an important role in determining the lifetime and the development of multinational corporations. Examining the structure of multinational corporations, we are able to observe companies gathered round the corpus, that is the country where the head office of the company is constructed. These companies spread all about the world to from a chain of companies belonging to the same multinational corporation. As companies become 'multinational' and undergo a structural change having reached far off places beyond their boundaries, the world of commerce has been transformed into a different shape, and this development is one of the most significant matters discussed in today's world. It is obvious that multinational corporations play a crucial role in the economic and social development of the world, but it is also true that they are of vital importance not only for the developed and less developed countries. Furthermore, multinational corporations carry out an important function in the process of cultural development since these corporations bring along their own culture (the culture of the country where the head office is constructed). When they are constructed in other countries. There can ofcourse be great differences between the culture of the host country and that of the main country and such differences produce some attractive and repelling factors for multinational corporations. In other words, engaging in business activities in different countries entail companies being introduced with different languages, habits, in short different beliefs and values as well as different problems. The differences observed among the business cultures of the USA, European countries, Japan and Asian countries are defined in this paper in detail. In the arrengement of this thesis, the cultural differences between the offices of the Ericsson company located in turkey, countries in America and Asia. It has been found out as a result that each company creates an institutional culture particular to itself. The Ericsson companies in foreign countries have attained success in production and marketing by developing their own institutional cultures. Being a leader in its own field for the last 121 years, the success of the Ericsson company is based on the common values and differences shared all around the world.
Keywords: ÇOK ULUSLU İŞLETMELER-YÖNETİM; Genel yönetim